Ethnic Density as a Key Factor to Narrow Health Disparities: A Case of American Indians and Alaska Natives. - Kim, Yong-Mi; Noyori-Corbett, Chie (Health & Social Work, 2024)
Out of all the racial groups in the United States, people who identify as American Indian and Alaska Native (AI/AN) have disproportionately worse health as a result of living in poverty. The preponderance of research connects poor health with a socioeconomic perspective, which might create prejudice against AI/AN. As already known, AI/AN's high rates of obesity, diabetes, and stroke in comparison with that of other ethnic groups are mainly derived from their impoverished economic conditions that have forced them to consume the food distributed by the U.S. government. When minority health is discussed generally, the ethnic density perspective explains a minority population's positive health despite low socioeconomic status. This perspective helps researchers and practitioners understand the connections of psychological and social factors with physical health and demonstrates positive health effects on minority groups. Despite the high correlation between ethnic density and health having been validated, little to no research has explored AI/AN's health from this perspective. Using 13,064 electronic health records, this research tests the relationship between AI/AN density and health outcomes. This article introduces an innovative analytical strategy (i.e. a data mining technique), which is ideal for discovering frequently appearing health outcomes in a group. The finding reveals positive relationships between health outcomes and AI/AN density.